Provision of Information Services to Prevent Intercultural Bulying Behavior - Mhd. Yogi Heriawan; Ali Daud Hasibuan (Edumaspul: Jurnal Pendidikan, 2024)
The aim of this research is to provide steps to prevent bullying behavior in students through information services. This research was conducted at SMAN 1 Stabat. The object of this research is class XI Ips students at SMAN 1 Stabat. The research method used in this research is descriptive qualitative. The data collection tools used were field observations, interviews with guidance and counseling teachers and providing information services to students. Data analysis in this research is qualitative descriptive using the Miles Huberman model. The results of this research are that the implementation of the information services provided really helps students in preventing bullying behavior between cultures that have differences in terms of accents or dialects. These differences greatly influence students' social environmental responses, becoming the subject of student jokes which results in bullying. With this information service, students can find out how to prevent intercultural bullying.